Peran Sistem Teknologi Temporary Immersion Bioreactor System (TIBS) terhadap Pertumbuhan dan Perkembangan Planlet Tiga Jenis Pisang (Musa spp.) - Eryuni Eryuni; Mir Alam Beddu; Baharuddin Baharuddin; Suyono Suyono (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
Conventional banana seedling propagation is often inefficient and time-consuming, so technological innovations are needed that can improve the speed and quality of seedling production. This study aims to assess the effect of liquid media-based Temporary Immersion Bioreactor System (TIBS) on the growth of planlets of three banana species. The research was conducted in a completely randomized design (CRD) involving two factors: media type (TIBS liquid media and solid media) and banana species (Barangan, Cavendish, and Kepok Tanjung), with three replications. The parameters observed included shoot emergence time, number of shoots per explant, number of leaves, and explant weight, which were analyzed using ANOVA and Honest Real Difference test (BNJ) at the 5% level. The results showed that TIBS liquid media significantly accelerated shoot emergence (11.89 days) compared to solid media (27 days). Barangan banana species produced the highest number of shoots (57.10 shoots) and the highest explant weight (33.44 grams), while the highest number of leaves was obtained in liquid media (68.40 leaves). The interaction between media type and banana type significantly affected all growth parameters. The conclusion of this study is that the liquid media-based TIBS system is able to improve the efficiency and quality of banana planlet growth, especially in the Barangan banana species, making it suitable for large-scale banana seedling development.